Croup in children in the period of the COVID-19 pandemic - M. A. Stroganova; G. P. Martynova; Ya. A. Bogvilene; K. O. Elmina; L. A. Ikkes; S. V. Evreimova; A. B. Belkina (Детские инфекции (Москва), 2023)
Croup syndrome remains one of the most common diseases in children, while being a life-threatening condition for the patient. Materials and methods. The paper presents the clinical and epidemiological features of croup in 79 children aged 0 months. up to 5 years of age hospitalized during the COVID-19 pandemic from January to September 2022. Results. In the age structure of patients, children of the first year of life predominated. The clinical picture of croup against the background of COVID-19 was usually characterized by an acute onset, febrile fever with the addition of symptoms of stenosing laryngotracheitis on the second and third days from the onset of the disease. The appointment of timely and adequate therapy at all stages of care is the key to a favorable outcome of croup in children.